Two new flavans from the trunk and leaves of Horsfieldia glabra. Issue 20 (17th October 2016) - Peng, Wei; Yang, Caiqiong; Zhan, Rui; Chen, Yegao
Abstract: Two new flavans, (2 R, 4 R )-4′-hydroxy-3′, 5′-methyl-6, 7-methylenedioxy-4- O -2′-cycloflavan (1 ), and (2 R, 4 R )-4′-hydroxy-3′-methyl-6, 7-methylenedioxy-4- O -2′-cycloflavan (2 ), along with six known compounds were isolated from the trunk and leaves of Horsfieldia glabra . Their structures were elucidated by means of extensive spectroscopic analysis. Compounds1 and2, together with4 –7 were assessed for their cytotoxicity against five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7 and SW-480), and the result showed that they had no activity. Abstract :